B cells inhibit bone formation in rheumatoid arthritis by suppressing osteoblast differentiation. Issue 1 (December 2018) - Sun, Wen; Meednu, Nida; Rosenberg, Alexander; Rangel-Moreno, Javier; Wang, Victor; Glanzman, Jason; Owen, Teresa; Zhou, Xichao; Zhang, Hengwei; Boyce, Brendan; Anolik, Jennifer; Xing, Lianping
Abstract The function of B cells in osteoblast (OB) dysfunction in rheumatoid arthritis (RA) has not been well-studied. Here we show that B cells are enriched in the subchondral and endosteal bone marrow (BM) areas adjacent to osteocalcin+ OBs in two murine RA models: collagen-induced arthritis and the TNF-transgenic mice. Subchondral BM B cells in RA mice express high levels of OB inhibitors, CCL3 and TNF, and inhibit OB differentiation by activating ERK and NF-κB signaling pathways. The inhibitory effect of RA B cells on OB differentiation is blocked by CCL3 and TNF neutralization, and deletion of CCL3 and TNF in RA B cells completely rescues OB function in vivo, while B cell depletion attenuates bone erosion and OB inhibition in RA mice. Lastly, B cells from RA patients express CCL3 and TNF and inhibit OB differentiation, with these effects ameliorated by CCL3 and TNF neutralization. Thus, B cells inhibit bone formation in RA by producing multiple OB inhibitors. B cells contribute to rheumatoid arthritis pathogenesis and bone erosion, but the underlying mechanisms are still unclear. Here the authors show, using mouse models and patient tissues, that B cells directly inhibit osteoblast differentiation by producing CCL3 and TNF, thereby providing a potentially new direction for arthritis therapy.